As we have already discussed exponent of exponent.

Let us try to solve an example, i.e., (2^{3})^{4}.

Here 2^{3} is multiplied itself for 4 times as 2^{3} x 2^{3} x 2^{3} x 2^{3} and

we can write as 2^{3+3+3+3 = 212,
in short we can also write (23)4 as 23 x 4 = 212.}

Therefore the result for (2^{3})^{4} is 2^{12}.

Let us try to solve few more examples :

- (4
^{3})^{2} - (3
^{4})^{6}
In the first example, i.e., (4

^{3})

^{2}= 4

^{3}x 4

^{3}= 4

^{3+3}= 4

^{6}. Or

(4^{3})^{2} = 4^{3 x 2} = 4^{6}

Therefore we get the result for (4^{3})^{2} as 4^{6}.

Coming to second example, i.e.,

(3^{4})^{6} = 3^{4} x 3^{4} x 3^{4} x 3^{4} x 3^{4} x 3^{4}

= 3^{4+4+4+4+4+4}

= 3^{24} (or)

(3^{4})^{6} = 3^{4 x 6}

=3^{24}

Therefore we get the result for (3^{4})^{6} as 3^{24}.

The examples have been illustrated in the video below :